2007
DOI: 10.21273/hortsci.42.3.642
|View full text |Cite
|
Sign up to set email alerts
|

Bell Pepper Fruit Yield and Quality as Influenced by Solar Radiation-based Irrigation and Container Media in a Passively Ventilated Greenhouse

Abstract: Frequent fertigation of soilless-grown bell pepper (Capsicum annuum L.) can increase fruit production, but development of fruit disorders may offset the increase in yield of first-quality (blemish-free) fruit in greenhouses with minimal environmental control. Fruit yield and quality were studied as affected by water volumes and nutrient concentration levels, delivered with irrigation events initiated after determined cumulative solar radiation levels, in ‘HA3378’ bell pepper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, for rockwool substrate in a free drainage system, Lee [111] recommended accumulated values of 0.8 MJ m −2 with a minimum rest time set (i.e., not irrigated if the target value is reached) between 20 min in bright and 50 min on dark days according to the crop growth phase. Additionally, for bell pepper in container growth with peat mix, perlite, and pine bark media, Jovicich et al [61] indicated that the first-quality fruit weight was enhanced at solar radiation integral levels of 0.34 MJ m −2 , while Lizarraga et al [52] proposed indoor values of 0.81 MJ m −2 for tomatoes grown in perlite in bags of 40 L. In addition, Nikolaou et al [60], working with cucumber in rockwool, indicated a 9% lower drainage amount between high and low irrigation frequency treatments (i.e., accumulated radiation outside greenhouse 1.3 MJ m −2 as opposed to 3 MJ m −2 ), with no negative impact on production.…”
Section: Time Clock Scheduling and The Accumulated Radiation Methodsmentioning
confidence: 99%
“…However, for rockwool substrate in a free drainage system, Lee [111] recommended accumulated values of 0.8 MJ m −2 with a minimum rest time set (i.e., not irrigated if the target value is reached) between 20 min in bright and 50 min on dark days according to the crop growth phase. Additionally, for bell pepper in container growth with peat mix, perlite, and pine bark media, Jovicich et al [61] indicated that the first-quality fruit weight was enhanced at solar radiation integral levels of 0.34 MJ m −2 , while Lizarraga et al [52] proposed indoor values of 0.81 MJ m −2 for tomatoes grown in perlite in bags of 40 L. In addition, Nikolaou et al [60], working with cucumber in rockwool, indicated a 9% lower drainage amount between high and low irrigation frequency treatments (i.e., accumulated radiation outside greenhouse 1.3 MJ m −2 as opposed to 3 MJ m −2 ), with no negative impact on production.…”
Section: Time Clock Scheduling and The Accumulated Radiation Methodsmentioning
confidence: 99%
“…Lateral shoots and flowers, just above the cotyledonary node, were also removed. The training system was applied to form a plant structure of two main branches (Alsadon et al, 2013) to form a ''V'' trellising canopy system (Jovicich et al, 2007). When pruning a main branch, only the flower on the branch node and its nearby leaf were left.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient solutions were supplied by a drip irrigation system, and the flow rate of the nutrient supply was 30 mL·min -1 per dripper. The plants were pruned to maintain two main stems, which were vertically trellised to a 'V' canopy system (Jovicich et al, 2007), and the additional plant management of pruning and training were carried out every week.…”
Section: Methodsmentioning
confidence: 99%